2015
DOI: 10.1371/journal.pone.0136066
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Contribution of Integrin to Cell Attachment on Poly(2-Methoxyethyl Acrylate) (PMEA) Analogous Polymers for Attachment-Based Cell Enrichment

Abstract: Cell enrichment is currently in high demand in medical engineering. We have reported that non-blood cells can attach to a blood-compatible poly(2-methoxyethyl acrylate) (PMEA) substrate through integrin-dependent and integrin-independent mechanisms because the PMEA substrate suppresses protein adsorption. Therefore, we assumed that PMEA analogous polymers can change the contribution of integrin to cell attachment through the regulation of protein adsorption. In the present study, we investigated protein adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 30 publications
7
74
0
Order By: Relevance
“…Recently, we reported that intermediate water content influenced the amount of protein adsorption. 29 We reported that increasing intermediate water content decreased protein adsorption amounts. As compared to intermediate water content in hydrated PMEA, the contents in hydrated PTHFA are lower.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 85%
“…Recently, we reported that intermediate water content influenced the amount of protein adsorption. 29 We reported that increasing intermediate water content decreased protein adsorption amounts. As compared to intermediate water content in hydrated PMEA, the contents in hydrated PTHFA are lower.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 85%
“…We found that PMEA and its analogs can suppress the protein adsorption on the substrates according to their intermediate water contents (Figure 9). 106,107 Thus, integrin-dependent cell adhesion was weakened on PMEA analogs which possess comparatively high intermedi- ate water contents (e.g., PMEA, poly{2-(2-methoxyethoxy) ethyl acrylate} (PMe2A), and poly[2-{2-(2-methoxyethoxy)-ethoxy}ethyl acrylate] (PMe3A) with the increase of their intermediate water contents. 107,108 Integrins play an important role in cell adhesion.…”
Section: Regulation Of Integrin Contribution For Cell Adhesion By Pmementioning
confidence: 99%
“…106,107 Thus, integrin-dependent cell adhesion was weakened on PMEA analogs which possess comparatively high intermedi- ate water contents (e.g., PMEA, poly{2-(2-methoxyethoxy) ethyl acrylate} (PMe2A), and poly[2-{2-(2-methoxyethoxy)-ethoxy}ethyl acrylate] (PMe3A) with the increase of their intermediate water contents. 107,108 Integrins play an important role in cell adhesion. Thus, cell adhesion is expected to be suppressed when integrin-dependent cell adhesion is weakened via the suppression of protein adsorption on the substrates.…”
Section: Regulation Of Integrin Contribution For Cell Adhesion By Pmementioning
confidence: 99%
“…68,70,71 Recently, we reported that substrates coated with poly(2-methoxyethyl acrylate) (PMEA) and its analogous polymers, which suppress protein adsorption, allowed the cells to adhere. [71][72][73][74] On PMEA-analogous polymer-coated substrates, the cells can adhere even in the presence of ethylenediaminetetraacetic acid (EDTA), an inhibitor of integrindependent cell adhesion. The few focal adhesions formed in cells cultured on PMEA-analogous polymer-coated substrates also indicate that the cells adhered via integrin-independent mechanisms.…”
mentioning
confidence: 99%
“…The few focal adhesions formed in cells cultured on PMEA-analogous polymer-coated substrates also indicate that the cells adhered via integrin-independent mechanisms. 72,73 The cells exhibited different functions on PMEA-analogous polymers-coated substrates compared with conventional culture substrates (e.g., tissue culture polystyrene). In particular, HepG2 cells were able to adhere on a PMEAcoated substrate via integrin-independent mechanisms and form a round shape that increased hepatocyte-specific functions such as albumin expression.…”
mentioning
confidence: 99%